Root and canal-specific features of maxillary first molars with fused roots - Beljić-Ivanović, Katarina; Karadžić, Branislav (Vojnosanitetski pregled, 2022)
Background/Aim. Maxillary first molars are one of the most challenging teeth for endodontic therapy. There are certain disparities in the number of roots and canals and canal interrelationships within the same root, particularly those with fused roots. The aim of the study was to assess ex vivo features of roots, root canals, and canal walls in maxillary first molars with fused roots. Methods. Out of the total of 366 maxillary first molars, 64 extracted maxillary first molars with fused roots were included in the study using cone-beam computed tomographic and microscopic examining. Tooth dimensions at the level of pulp chamber floor, number, location and distance between orifices, number and canal morphology, canal wall thickness, and features of apical foramina were examined and measured. Results. The incidence of maxillary first molars with root fusion was 17.5%, of which 60.0% was palatal fused to distobuccal root. At the level of the pulp chamber floor, the bucco-palatal dimension was significantly larger at 10.4 mm than M-D with 7.0 mm. Four canal orifices were detected in 65.6%, with the shortest distance of 1.95 mm between MB1 and MB2. In fused roots, two or three canals most frequently correlated strongly with the number of major apical foramina. No fusion of canals was found in fused roots. The thinnest canal wall in the mesiobuccal and distobuccal fused root was mesial with 1.25 mm, and distal with 1.31 mm, while for the palatal root, the thinnest was the palatal wall with 1.97 mm. Two or three large apex foramina were registered with a significant correlation with the number of canals in the fused root. Conclusion. The most frequent type of fusion was between the palatal and distobuccal roots. Bucco-palatal dimension at the level of the pulp chamber floor was significantly larger than the mesiodistal, with the shortest inter-orifice distance between the MB1 and MB2 orifice. The number of canals was either two or three, coinciding with the number of major apical foramina. There was no fusion of the canals in fused roots. The thinnest canal wall was either mesial or distal.